2022
DOI: 10.1002/mgg3.1894
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype and genotype spectrum of variants in guanine nucleotide exchange factor genes in a broad cohort of Iranian patients

Abstract: Background Guanine nucleotide exchange factors (GEFs) play pivotal roles in neuronal cell functions by exchanging GDP to GTP nucleotide and activation of GTPases. We aimed to determine the genotype and phenotype spectrum of GEF mutations by collecting data from a large Iranian cohort with intellectual disability (ID) and/or developmental delay (DD). Methods We collected data from nine families with 20 patients extracted from Iranian cohort of 640 families with ID and/or DD. Next‐generation sequencing (NGS) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 88 publications
1
3
0
Order By: Relevance
“…The ITSN1 variant p.(Trp949*) identified in this study lies in the SH3 domain of and in close proximity of previously known variants [p.(Met948Val*41) and p.(Tyr965*)] for ASD 1,4 . Furthermore, biallelic variants in the ITSN1 gene have also been known to cause autosomal recessive intellectual disability (ARID) 5 …”
Section: Figuresupporting
confidence: 68%
“…The ITSN1 variant p.(Trp949*) identified in this study lies in the SH3 domain of and in close proximity of previously known variants [p.(Met948Val*41) and p.(Tyr965*)] for ASD 1,4 . Furthermore, biallelic variants in the ITSN1 gene have also been known to cause autosomal recessive intellectual disability (ARID) 5 …”
Section: Figuresupporting
confidence: 68%
“…In the HGMD Professional version, the phenotypes listed as being associated with DENND2A were 'congenital heart disease' and 'intellectual disability'. It has been reported that mutations in DENND2A are associated with multiple phenotypes, including ischemic stroke, Parkinson's disease and non-syndromic intellectual disability (Lang et al 2019;Mosallaei et al 2022). However, we did not nd any overlapping genes between the UK Biobank and BioMe BioBank results for genes associated with both EP and CHD (likely due to phenotyping and genotyping differences between the biobanks, as well as sample sizes; see Methods).…”
Section: Replication Study Using Mount Sinai Biome Biobank Whole Exomesmentioning
confidence: 99%
“…In HGMD Professional, the phenotypes listed as being associated with DENND2A were 'congenital heart disease' and 'intellectual disability'. It has been reported that mutations in DENND2A are associated with multiple phenotypes, including ischemic stroke, Parkinson's disease, and non-syndromic intellectual disability (Lang et al 2019;Mosallaei et al 2022). However, we did not find any overlapping genes between the UK Biobank and BioMe BioBank results for genes associated with both EP and CHD (likely due to phenotyping and genotyping differences between the biobanks, as well as sample sizes; see Methods).…”
Section: Replication Study Using Mount Sinai Biome Biobank Whole Exomesmentioning
confidence: 99%